THE APPLICATION OF HUMAN RESOURCES MANAGEMENT DESIGN FOR ENHANCING OUTPUT IN AGRICULTURAL COMPANIES - Bashayreh, Anas M. (The journal of contemporary issues in business and government, 2023)
The present stateofHR management duties and responsibilities as theyrelate to Agricultural Companies and design is discussed in this article. Furthermore, based on the findings of a main study, it describes the functions of HR in organizations that have altered their HR departments in terms of HR Management Design concepts, both theoretically and practically. The purpose of this paper is to present the roles and duties in HR structures inside organizations, as well as the effects of these changes on HR departments' effectiveness. Another purpose of the article is to define the tasks and obligations of the newly created HR Management Design job in these firms. It also houses an organization with one of the most well-remodeled HR departments in the country, and whose internal clientele evaluate its services as good.